THE MAIN RESULTS OF COOPERATION BETWEEN THE V.A. NASONOVA RESEARCH INSTITUTE OF RHEUMATOLOGY AND RESEARCH CENTERS OF EUROPE WITHIN THE EUSTAR (EULAR SCLERODERMA TRIALS AND RESEARCH GROUP) IN SYSTEMIC SCLEROSIS - L. P. Ananyeva; M. N. Starovoitova; S. Sh. Shabanova (Научно-практическая ревматология)
The major goals of the EUSTAR (EULAR Scleroderma Trials And Research group) are to coordinate and centralize systemic sclerosis (SS) researches in Europe, to reach a consensus in the standards of evidence-based medicine for patient management, to enhance treatment efficacy, and to improve quality of life in patients and prognosis. Under the aegis of the EUSTAR, more than 100 centers have combined their efforts to solve basic research problems, to study the clinical aspects of the disease, and to conduct clinical trials. The major task of their activities has been to follow-up and timely treat SS patients examined according to a standard protocol, and to accumulate information in the unified European database that includes more than 10,000 patients now. The V.A. Nasonova Research Institute of Rheumatology has formed a cohort of 220 patients with SS, of whom 90–100 persons are annually followed up.The main joint projects implemented have shown the present-day course of SS, studied the causes of death, and characteristics of patient subgroups (juvenile scleroderma, SS in the elderly, damage of the lung, heart, gastrointestinal tract, etc.). New diagnostic criteria for SS and an algorithm for its very early, preclinical diagnosis have been proposed. An analysis of the first 3656 patents with SS has revealed the major clinical characteristics of its diffuse and limited forms at the present stage. Pooled patient data have been used in international multicenter projects whose results are given in joint publications. The results of EUSTAR projects with the participation of the V.A. Nasonova Research Institute of Rheumatology are covered in 28 articles. Analysis of the results of EULAR/EUSTAR researches gives grounds to hold that the early diagnosis and timely detection of visceral injuries and the use of current therapy standards may assist in improving the quality of life of patients as well as in reducing the severity of SS and its mortality rates.